Participation in online research: towards a typology of research subjects with regard to digital access and literacy - Hannemann, Matthias; Henn, Sebastian; Schäfer, Susann (International journal of qualitative methods, 2023)
The Covid-19 pandemic has severely impacted empirical research practices relying on face-to-face interactions, such as interviews and group discussions. Confronted with pandemic management measures such as lockdowns, researchers at the height of the pandemic were widely limited to the use of online methods that did not enable direct contact with their research subjects. Even as the pandemic subsides, online data collection procedures are being widely applied, in many cases possibly recklessly. In this paper, we urge the implementation of a reflective approach to online research. In particular, we argue that both digital access and the research subjects’ digital literacy affect participation in online research and thus also the quality of the research. By combining these two dimensions, we develop a typology of four types of research subjects (digital outcasts, illiterates, sceptics and natives) that allows researchers to adapt their data collection to the specifics of each research situation. We illustrate these types in the context of our own research projects and discuss them with regard to three main challenges of empirical research, i.e., acquiring participants, establishing a basis for conversation, and maintaining ethical standards. We conclude by developing recommendations that help researchers to deal with these challenges in the context of online research to avoid unintended biases.